0375 A Novel Dual Orexin Receptor Antagonist (ACT-541468) to Treat Insomnia: A Randomized, Double-Blind, Placebo-Controlled, Active-Reference Phase 2 Study. (12th April 2019) - Dauvilliers, Yves; Zammit, Gary; Fietze, Ingo; Mayleben, David; Kinter, Dalma Seboek; Pain, Scott; Hedner, Jan
Abstract: Introduction: Orexins are involved in the regulation of sleep and wakefulness. The primary objective of this Phase 2 study was to investigate the dose-response relationship of ACT-541468 on sleep variables in subjects with insomnia disorder. Methods: Eligible adults (≤64 years) with insomnia disorder (Diagnostic and Statistical Manual of Mental Disorders, 5 th Edition criteria) were randomized (1:1:1:1:1:1) to receive, 5, 10, 25, and 50 mg ACT-541468, placebo or 10 mg zolpidem for 4 weeks. Main efficacy endpoints were the change from baseline (placebo run-in) to Days1&2 for wake after sleep onset (WASO; primary) and latency to persistent sleep (LPS; secondary). The dose-response of ACT-541468 was evaluated using MCP-Mod methodology. Results: Of 1005 subjects screened, 360 (median age 47 [range, 36-53]; 64% female) were randomized. A significant dose-response of ACT-541468 was demonstrated for WASO (p≤0.0007). Observed mean reductions from baseline to Days 1&2 for WASO were −28.99, −33.75, −39.64, and −45.49 min for ascending ACT-541468 doses (placebo, −20.98 min; zolpidem, −31.23 min) and were sustained at Days28&29 (−37.76, −43.74, −39.84, −46.97 min for ascending ACT-541468 doses [placebo, −33.80 min; zolpidem, −37.08 min]). A significant dose-response for LPS at doses 10 mg and above was detected (p<0.05). Observed changes in mean LPS from baseline to Days1&2 were −26.88, −29.31, −36.14, and −36.41 min for ascending ACT-541468 doses (placebo, −22.02 min; zolpidem, −45.12 min). Reductions in LPS were sustained at Days28&29. ACT-541468 treatment was well-tolerated at all doses, with no evidence of dose-dependent adverse effects. Treatment-emergent adverse events (TEAEs) were reported in 35%, 38%, 38%, and 34% subjects treated with 5, 10, 25, and 50 mg ACT-541468, respectively (30% for placebo; 40% for zolpidem). The main TEAEs across all groups were headache, somnolence, and nasopharyngitis. No signs of next-day residual effects or rebound insomnia were observed. Conclusion: ACT-541468 demonstrated a significant dose-response for WASO and LPS compared with placebo and was well-tolerated without dose-dependent safety concerns or residual negative next-day effects. Phase 3 evaluation of ACT-541468 in adults with insomnia is ongoing. Support (If Any): None